โครงสร้างและสมบัติการเคลื่อนที่ของอิเล็กโทรไลต์ในแบตเตอรี่สังกะสีไอออนฐานน้ำ - ณัฐวรรณ แสงนวกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Recently, zinc-ion batteries (ZIBs) have emerged as a promising candidate to lithium-ion batteries (LIBs), especially for grid-scale applications, owing to high compatibility with aqueous electrolytes, further providing the system with low cost, high safety, and environmental friendliness. The system performance of aqueous ZIBs depends on the electrolytes. Efficient and accurate molecular simulations are significant importance not only to elucidate electrolyte behavior and transport mechanism, but also for fundamental molecular insights and rational guidance of experimental developments. In this work, a molecular dynamics (MD) was employed to investigate structural features and transport properties of ions in aqueous electrolytes: zinc (II) triflimide (Zn(TFSI)₂ and zinc (II) triflate (Zn(OTf)₂). All simulations were carried out at ambient conditions. When the concentration of Zn(TFSI)₂ electrolyte increases, the Zn²⁺diffusivity decreases, leading to lower the ionic conductivity. At concentration of 1 M, the ionic conductivity is maximum. At 2 M Zn(TFSI)₂ concentration, the Zn²⁺ ions are surrounded by ~5 water molecules and the salt-water complexes like contact ion pairs are dominant. Furthermore, for 1 M concentration, the Zn(OTf)₂ ionic conductivity is higher than that obtained from Zn(TFSI)₂ system. The results suggest that the Zn²⁺ ions have stronger interaction with OTf– than TFSI– because of the bulky TFSI– anions.